Diagnostics of coronary heart disease in patients with diabetes mellitus - Kalarus, Zbigniew; Zielińska, Teresa; Pluta, Sławomir (Przewodnik Lekarza/Guide for GPs, 2006)
Diabetes mellitus is a well known risk-factor of development of atherosclerosis. Specific features of coronary heart disease in diabetic patients are early manifestation of disease, oligosymptomatic course, different anatomical type of atherosclerosis and worse outcome compared to patients without diabetes. Non-invasive methods used in diagnostics of coronary heart disease in diabetics include electrocardiographic exercise test, stress echocardiography, perfusion scintigraphy of myocardium and multislice computer tomography. Non-invasive diagnostics allows to define the indications for coronarography, which is an invasive method of coronary arteries imaging. Coronary angiography still remains a „gold standard” in diagnostics of coronary heart disease, also in diabetic patients.